KETERLIBATAN TEKNOLOGI KOMUNIKASI DAN INFORMASI (TIK) DALAM MENINGKATKAN KUALITAS PEMBELAJARAN DI JENJANG SEKOLAH DASAR - Tiarani, Siti Dhinda; Hidayati, Abna; Helsa, Yullys (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to explore and investigate the potential for the involvement and utilization of Information and Communication Technology (ICT). Involving 21st-century learning, the study also examines the role of ICT in improving the quality of education at the elementary school level. The method used in this research is a descriptive-qualitative method with a literature review approach. The researcher analyzed several articles from relevant journals related to previous research discussions. Data were collected by searching for various articles in online journals using Google Scholar. The conclusion of this research indicates that the involvement of ICT brings significant transformation in education by enhancing the quality of the learning process and outcomes.